ВНЕСОК ПРОФЕСОРА П. А. ТАЛЬКО-ГРИНЦЕВИЧА У РОЗВИТОК ТЕОРІЇ ТА МЕТОДИКИ НАВЧАННЯ ФІЗИКИ В УКРАЇНІ - Головко, Микола (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті на основі вивчення та аналізу навчально-методичних праць, наукових джерел та архівних матеріалів вперше системно досліджується розвиток питань методології та методики навчання фізики у працях П. А. Талько-Гринцевича. Висвітлюється науково-педагогічна діяльність видатного вченого, його внесок у формування змісту навчання фізики, підручникотворення та вирішення актуальних питань вітчизняної дидактики фізики. Наголошується щодо важливості досліджень ученого як в історико-методичному контексті, так і для побудови сучасних дидактичних систем навчання фізики. Обґрунтовується доцільність позиціонування діяльності колективу методистів-фізиків Одеси цього періоду з функціонуванням наукової школи методики фізики, започаткованої Ф. Н. Шведовим. В статье на основе изучения и анализа учебно-методических работ, научных источников и архивных материалов впервые системно исследуется развитие вопросов методологии и методики обучения физике в трудах П. А. Талько-Гринцевича. Освещается научно-педагогическая деятельность выдающегося ученого, его вклад в формирование содержания обучения физике, создание учебников и решение актуальных вопросов отечественной дидактики физики. Отмечается важное значение исследований ученого как в историко-методическом контексте, так и для построения современных дидактических систем обучения физике. Обосновывается целесообразность позиционирования деятельности коллектива методистов-физиков Одессы этого периода с функционированием научной школы методики физики, основанной Ф. Н. Шведовым. The article based on the study and analysis of teaching activities, scientific sources and archival materials for the first time systematically investigated the development of the methodology and methods of teaching physics in the works of P. A. Talc-Grintsevich. Highlights the research and teaching activities of the outstanding scientist, his contribution to the development of the content of teaching physics, textbooks and current issues of domestic didactics of physics. Analyzed scientific papers practitioner in which the necessity of forming in pupils and students the ability to use theoretical and practical methods of study of physical phenomena, the role of scientific hypotheses. The features in the implementation of the author’s approach in building content and methodical device physics textbook «Outline of physics». The approaches to solving the problem of the formation of scientific concepts in physics that their coverage during the training process, pupils and students get acquainted with the theoretical and experimental methods of knowledge of physical phenomena are analyzed. It notes the importance of scientific research in historical and methodological context, and for the construction of modern physics didactic training systems. The expediency of the collective positioning activities of Methodist in physicist is grounded in this period in Odessa with the functioning of the scientific school of physics techniques founded by F. N. Shvedov.